Status kesehatan ibu hamil pada era jaminan kesehatan nasional di kota denpasar: Health status of pregnant women in the era of national health insurance in denpasar city - Arini, Ketut Novia; Widiastuti, Ni Made Rai (Bali Medika Jurnal, 2021)
The national health insurance program for midwifery and neonatal services is an effort to guarantee and protect the process of pregnancy, childbirth, postpartum, postpartum bleeding and family planning services as well as complications related to pregnancy, childbirth, postpartum and family planning.  With the national health insurance program, it is hoped that the health status of pregnant woman in Indonesia can increase and the achievement of the Sustainable Development Goals in terms of reducing the maternal mortality rate can be achieved. This study aims to determine the health status of pregnant women in the era of national health insurance in Denpasar City. This study used a quantitative descriptive research design. This research was conducted in seven primary health care in Denpasar City. This research was conducted for one month, namely in April 2020. From the results of the study, it was found that most pregnant women aged 20-35 years, including in the multigravida category, had gestational age in the third trimester and were not participants in the health social security administering that received contribution from the government. There are still pregnant women who are included in the Low High Mother (LHM) category, chronic energy deficiency, anemia, hypertension, have positive urine protein, and receive blood booster tablet of less than 90 tablets. There were not pregnant women with uterine fundal height and abnormal fetal hearth rate. It was not found that pregnant women were infected with sexually transmitted infections and HIV/AIDS.